Novel Remediation Technique for Stabilizing the Damaged Slopes of Kenyir Dam - Hafez M.; Jine C.Y.; Muda Z.C.; Sidek L.M.; Yassin A.M.; Eldin M.M. (Natural Sciences Publishing, 2025)
This study evaluates the engineering properties of a novel type of reinforced PVC-encased micropile made of an expanded mixture (PUCR) of polyurethane resin (PU) and crumb rubber (CR) for Kenyir dam slopes stabilization. Two types of PUCR micropiles were tested: one containing 4.0 kg/m of PU and another with 2.0 kg/m of PU, both with varying ratios of CR from 0% to 30%. Compressive and flexural strength tests were conducted. Results showed that a 1:1 ratio of Polyol to Isocyanate in PU yielded the best compressive strength. For 4 kg/m PUCR micropiles, strength decreased as CR ratio increased, while for 2 kg/m micropiles, strength increased with CR ratio up to 10%. The study concludes that PUCR micropiles demonstrate good flexural strengths and may offer installation advantages for reinforcing unstable slopes, especially in areas with space and access constraints. However, proper sizing and CR ratio optimization are crucial for enhancing structural integrity and performance. ? 2024 NSP Natural Sciences Publishing Cor.